Configuration the Thought of Islamic Law Throught Social Media in Indonesia - Sonafist, Y. (International Journal of Law and Society, 2022)
This study shows the reasoning behind Islamic law, which has recently become popular, along with the popularity of preachers through social media. Three themes of analysis are discussed in this study: the law of wishing Merry Christmas, the law of celebrating birthdays, and the law of music. Judging from the source, this research is text research. The text to be studied is in the form of lectures by well-known preachers on YouTube social media. This study uses an interdisciplinary approach, which combines discourse analysis with Islamic legal philosophy (ushul fiqh). The mapping of Islamic legal reasoning in this study is seen from two aspects, namely, the aspect of legal status and the aspect of legal methodology. This study found that the contestation occurred from legal status, as evidenced by the diversity of sources' opinions on the three issues examined here. In the methodological aspect, the contestation continues, both at the stage of the reasoning model, discovering maqshid sharia, and developing the theory of Islamic law. This study also found that using reasoning models positively correlated with the legal status they conveyed.